2004
DOI: 10.1523/jneurosci.4934-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A Activation Promotes Plasma Membrane Insertion of DCC from an Intracellular Pool: A Novel Mechanism Regulating Commissural Axon Extension

Abstract: Protein kinase A (PKA) exerts a profound influence on axon extension during development and regeneration; however, the molecular mechanisms underlying these effects of PKA are not understood. Here, we show that DCC (deleted in colorectal cancer), a receptor for the axon guidance cue netrin-1, is distributed both at the plasma membrane and in a pre-existing intracellular vesicular pool in embryonic rat spinal commissural neurons. We hypothesized that the intracellular pool of DCC could be mobilized to the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
144
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(170 citation statements)
references
References 56 publications
24
144
1
1
Order By: Relevance
“…Thus, we found that the PLC signaling cascade activated by the physiological agonist adenosine is the critical invasion effector acting through Rho/ROK-independent mechanisms and the Ca 2 þ -dependent myosin light chain kinase that is believed to promote the contractility of the actin cytoskeleton, as shown previously in our laboratory (Nguyen et al, 2005). Both adenosine and the A2B-R are linked to cAMP pathways and to the recruitment of DCC receptors from an intracellular pool to the cell surface, in a netrin-dependent manner (Bouchard et al, 2004). In contrast, we have shown that the proinvasive activity of netrin is determined by PKA, Rho/ROK and PI3K-dependent pathways via a PLC-independent mechanism.…”
Section: Dcc/netrin In Cancer Cell Invasion and Metastasis S Rodriguementioning
confidence: 63%
“…Thus, we found that the PLC signaling cascade activated by the physiological agonist adenosine is the critical invasion effector acting through Rho/ROK-independent mechanisms and the Ca 2 þ -dependent myosin light chain kinase that is believed to promote the contractility of the actin cytoskeleton, as shown previously in our laboratory (Nguyen et al, 2005). Both adenosine and the A2B-R are linked to cAMP pathways and to the recruitment of DCC receptors from an intracellular pool to the cell surface, in a netrin-dependent manner (Bouchard et al, 2004). In contrast, we have shown that the proinvasive activity of netrin is determined by PKA, Rho/ROK and PI3K-dependent pathways via a PLC-independent mechanism.…”
Section: Dcc/netrin In Cancer Cell Invasion and Metastasis S Rodriguementioning
confidence: 63%
“…Calcium signaling has an effect on the growth rate of growth cones, first characterized as a narrow extracellular calcium concentration range favorable for growth [43,[60][61][62]. Surprisingly, calcium transients [63,64] and calcium entry through mechanosensitive channels slow axon growth, whereas calcium release from ER stores enhances growth [41]. The relation between calcium transients and cAMP signaling may be different between the central domain of the growth cone and its filopodia [19].…”
Section: Reviewmentioning
confidence: 99%
“…PKA can effect the insertion of guidance cue receptors into the plasma membrane (Bouchard et al, 2004). Both NGF and MAG can engage p75 NTR as part of their receptor complex in certain contexts raising the possibility that receptor dynamics may be altered by PKA activation at the site of ligand binding.…”
Section: -3-3 Expression In Growth Conesmentioning
confidence: 99%
“…How the activation state of cytoskeletal regulatory proteins is spatially and temporally regulated is an important question which has only been partially elucidated. Local translation, insertion and removal of receptors at the plasma membrane as well as receptor silencing all affect growth cone responses (Stein and TessierLavigne, 2001;Bouchard et al, 2004;Kim et al, 2005;Lin and Holt, 2007). Further, regulating intracellular concentrations of cyclic nucleotides affects whether neuronal processes are attracted or repelled by guidance cues in vitro and in vivo Song et al, 1998;Song and Poo, 1999;Polleux et al, 2000;Shewan et al, 2002;Nishiyama et al, 2003).…”
Section: Introductionmentioning
confidence: 99%